Organizational hierarchy and structural diversity of microvascular pericytes in adult mouse cortex. Issue 3 (March 2019) - Grant, Roger I; Hartmann, David A; Underly, Robert G; Berthiaume, Andrée-Anne; Bhat, Narayan R; Shih, Andy Y
Smooth muscle cells and pericytes, together called mural cells, coordinate many distinct vascular functions. Canonically, smooth muscle cells are ring-shaped and cover arterioles with circumferential processes, whereas pericytes extend thin processes that run longitudinally along capillaries. In between these canonical mural cell types are cells with features of both smooth muscle cells and pericytes. Recent studies suggest that these transitional cells are critical for controlling blood flow to the capillary bed during health and disease, but there remains confusion on how to identify them and where they are located in the brain microvasculature. To address this issue, we measured the morphology, vascular territory, and α-smooth muscle actin content of structurally diverse mural cells in adult mouse cortex. We first imaged intact 3D vascular networks to establish the locations of major gradations in mural cell appearance as arterioles branched into capillaries. We then imaged individual mural cells occupying the regions within these gradations. This revealed two transitional cells that were often similar in appearance, but with sharply contrasting levels of α-smooth muscle actin. Our findings highlight the diversity of mural cell morphologies in brain microvasculature, and provide guidance for identification and categorization of mural cell types.